Effect of pine (Pinus Sylvestris) bark dust on particleboard thickness swelling andinternal bond : Utjecaj dodatka prašine napravljene od borove kore na debljinsko bubrenje i čvrstoću raslojavanja ploča iverica - Medved, Sergej (Array, 2019)
Increasing demand for wood resulted in competition between different branches of wood-based production. High intensity production, like the production of wood-based panels, is forced to look for other lignocellulosic resources. Bark is a possible source for wood-based panel industry, especially for particleboards. Bark chips were crushed into bark dust, which were used for the production of single-layer particleboards. The share of bark dust was 0 %, 0.5 %, 1 %, 5 % and 10 %. The boards were tested on thickness swelling (immersion in water, exposure to humid conditions) and internal bond. The highest internal bond was determined in the particleboard with 1 % bark share. Thickness swelling of boards with added bark was higher compared to boards without bark. The highest swelling was observed in boards with 10 % bark dust (immersion in water) or 5 % (humid conditions). Bark based boards absorbed less water.